Impact of Team Competencies on Performance - Puente-Palacios, Katia (2017)
Job competences have been traditionally understood as individual properties. However, due to the increasing implementation of teams in organizations, is defended also that competences can be treated as a collective characteristic. The main goal of this study was demonstrate that competencies are collective properties and they act as predictors of teamperformance. The empirical study was undertaken with information collected from 51 Brazilian airports which tasks are organized on teams (106; 3 until 33 members). Team members offered information about competences, and leaders offered information about performance of teams. The results demonstrated that collective competencies explain around 20% of the performance. Based on those results, team competences are defended as collective characteristic that predict results of teams.